Masahista The masseur - Mendoza, Brillante 1960-.; Agbayani Pastor, Boots S.; Jose, Jaclyn; Paule, Alan.; Martin, Coco.; Luna, Katherine; Rivero, Paolo; King, Kristopher; Miranda, R. U.; Lapuz, Ferdinand; Gee Films International; Centerstage Productions ([Los Angeles, Calif.] Gee Films Productions Int'l., 2003)
"In Manila, 20-year-old Iliac and his hot, young male co-workers give massage and a whole lot more to their gay clientele. When Iliac's philandering father passes away, the young man must reconcile his career as a sex worker with his role as son and brother to his grieving Mom and siblings"--Container.
"Based on the original story by Ferdinand Lapuz."
Special features: theatrical trailer, documentary featurette (The masseur at the Toronto Int?l Film Festival), photo gallery.
Editor, Herbert Navasca ; music, Jerrold Tarog ; directors of photography, Timmy Jimenez, Monchie Redoble.
Jaclyn Jose, Alan Paule, Coco Martin, Katherine Luna, Paolo Rivero, Kristopher King, RU Miranda.
DVD, NTSC, region 1; widescreen format; Dolby digital 2.0 stereo and 5.1 surround.
In Tagalog, Pampango, and English, with optional English, French, and Spanish subtitles.
Keywords: Male prostitutes -- Philippines -- Manila -- Drama; Gay men -- Sexual behavior -- Philippines -- Manila -- Drama; Families -- Philippines -- Drama; Feature films